Finding Gold in Intranet Data: A Comparison of Mined and Surveyed Social Networks - Zhao, Chen; Liu, Baozhong (Proceedings of the International AAAI Conference on Web and Social Media, 2010)
The goal of this research is to identify to what extent a social network extracted from public intranet data sources represents the actual interactions among people as reflected by a self-reported survey. We describe a case study we conducted within a large multinational software company comparing social networking information gathered from a traditional socio-centric network analysis (SNA) survey with various public intranet sources. Our results suggest that the value which automatically harvested social networks represent good percentage of actual ties with less privacy concern and low cost.